The tumor suppressor Hic1 maintains chromosomal stability independent of Tp53 - Szczepny, Anette (Oncogene, 2018)
Hypermethylated-in-Cancer 1 (Hic1) is a tumor suppressor gene frequently inactivated by epigenetic silencing and loss-of-heterozygosity in a broad range of cancers. Loss of HIC1, a sequence-specific zinc finger transcriptional repressor, results in deregulation of genes that promote a malignant phenotype in a lineage-specific manner. In particular, upregulation of the HIC1 target gene SIRT1, a histone deacetylase, can promote tumor growth by inactivating TP53. An alternate line of evidence suggests that HIC1 can promote the repair of DNA double strand breaks through an interaction with MTA1, a component of the nucleosome remodeling and deacetylase (NuRD) complex. Using a conditional knockout mouse model of tumor initiation, we now show that inactivation of Hic1 results in cell cycle arrest, premature senescence, chromosomal instability and spontaneous transformation in vitro. This phenocopies the effects of deleting Brca1, a component of the homologous recombination DNA repair pathway, in mouse embryonic fibroblasts. These effects did not appear to be mediated by deregulation of Hic1 target gene expression or loss of Tp53 function, and rather support a role for Hic1 in maintaining genome integrity during sustained replicative stress. Loss of Hic1 function also cooperated with activation of oncogenic KRas in the adult airway epithelium of mice, resulting in the formation of highly pleomorphic adenocarcinomas with a micropapillary phenotype in vivo. These results suggest that loss of Hic1 expression in the early stages of tumor formation may contribute to malignant transformation through the acquisition of chromosomal instability.